Case Report: Exclusive localization of Leishman-Donovan bodies in neutrophils on peripheral blood smear in a patient with systemic lupus erythematosus - Ma, Fucun; Zhang, Ruixue; He, Meilin; Li, Jia; Bai, Mingjian; Liang, Guowei; Liu, Xuekai (Frontiers in Medicine, 2025)
BackgroundVisceral leishmaniasis (VL) is a life-threatening parasitic infection transmitted by sand flies. Its clinical manifestations can overlap with those of autoimmune diseases, such as systemic lupus erythematosus (SLE). Traditional diagnostic approaches, like bone marrow aspiration, have limited sensitivity for detecting the parasite in peripheral blood. Immunosuppressed patients often present atypically, further complicating diagnosis. Rarely, Leishmania amastigotes (Leishman-Donovan bodies) can be found within neutrophils, which challenges the conventional view that the parasite primarily infects monocytes/macrophages.Case presentationA 73-year-old male patient with a history of SLE was on immunosuppressive therapy. The patient presented with persistent pancytopenia and splenomegaly. The prior SLE diagnosis contributed to a delay in recognizing VL. A meticulous examination of the peripheral blood smear first revealed Leishman-Donovan bodies within neutrophils, providing the critical diagnostic clue. This finding prompted further investigations, and the diagnosis was subsequently confirmed by the combination of bone marrow aspiration and serological testing. His immunosuppressed state likely masked typical inflammatory responses and increased his vulnerability to this opportunistic infection, highlighting the difficulty in distinguishing between autoimmune and parasitic diseases.ConclusionThis case underscores the diagnostic challenge of VL in immunosuppressed patients. Symptom overlap with autoimmune disorders and atypical parasite locations (e.g., within neutrophils) can delay diagnosis. Morphological examination of blood and bone marrow remains crucial for detecting rare pathogens. In endemic areas, clinicians should routinely check for parasites within neutrophils to reduce misdiagnosis. Future studies should explore neutrophil-parasite interactions and improve infection monitoring strategies in immunocompromised hosts.